PEMBERDAYAAN HOME INDUSTRY: HAND CRAFT DARI BAMBU MENUJU SMART COMMUNITY DI DESA BARABALI KABUPATEN LOMBOK TENGAH - Juniawan, Alvin; Sahid, Ashabul; Aulia, Fitria; Husna, Erlina Urwatul; Wahyudi, Hari; Jody Prayoga, Lalu Muhammad; Gde Paradatu, Lalu Puri Agung; Andini, Arista Suci (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
This community service is held to improve the quality of human resources and the economy of the people in Barabali Village by raising the potential of Barabali Village which has an abundance of natural resources in the form of bamboo. The availability of raw materials, in this case bamboo, is a supporting factor that provides the opportunity and potential to be used as a product that has economic value. Based on field observations, the wealth of natural resources in the form of bamboo has not been utilized optimally. The business that has been running so far does not have a variety of product varieties so that its market share is limited, production creativity is still low so it does not have high selling power. In this activity, innovations and new creations of bamboo products were introduced which were adapted to the latest market trends. This will open up a new market for the creative industry, especially bamboo handicrafts and can have a positive impact on the people's economy. The participants in this Community Empowerment activity were members of the Barabali Village Women Farmers Group (KWT) with a high level of participation and this had a positive impact on the implementation of the activity. At the end of the activity, the participants gained soft skills in making products and were able to produce several variations of bamboo handicraft products in the form of door ornaments, night lamps and bamboo mugs.